Metal-mediated alkynediol cycloisomerization: first and second generation formal total syntheses of didemniserinolipid B - Das, Shyamsundar; Induvadana, Boddeti; Ramana, C. V. (Tetrahedron, 2013)
A formal total synthesis of didemniserinolipid B was developed by employing a regioselective metal-mediated 6-endo-dig alkynol-cycloisomerization reaction. Two routes for the synthesis of key Burke's intermediate have been developed. Our initial approach involved the introduction of a C-17-allcynol followed by Pd-mediated cycloisomerization and then coupling with the serinol unit prior to the introduction of an alpha,beta-unsaturated ester unit through selective oxidation of 1 degrees-OH followed by a two-carbon Wittig homologation. Alternatively, the second generation strategy featuring the serinol coupling with the C-17-alkynol followed by alkyne addition to the epoxide and subsequent Au-mediated cycloisomerization of an acetonide protected alkynediol unit has been executed. This approach has avoided several late stage protection-deprotection events. (C) 2012 Elsevier Ltd. All rights reserved.
Keywords: Alkynol-cycloisomerization; Bicyclic ketal; Gold catalysis; Palladium catalysis; Zipper reaction